2013
DOI: 10.2337/dc13-0323
|View full text |Cite
|
Sign up to set email alerts
|

Linagliptin Lowers Albuminuria on Top of Recommended Standard Treatment in Patients With Type 2 Diabetes and Renal Dysfunction

Abstract: OBJECTIVEPreclinical data suggest that linagliptin, a dipeptidyl peptidase-4 inhibitor, may lower urinary albumin excretion. The ability of linagliptin to lower albuminuria on top of renin-angiotensin-aldosterone system (RAAS) inhibition in humans was analyzed by pooling data from four similarly designed, 24-week, randomized, double-blind, placebo-controlled, phase III trials.RESEARCH DESIGN AND METHODSA pooled analysis of four completed studies identified 217 subjects with type 2 diabetes and prevalent albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
233
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 272 publications
(256 citation statements)
references
References 39 publications
16
233
2
5
Order By: Relevance
“…Urine albumin levels were elevated in STZ mice, and linagliptin treatment suppressed the trend of the urine albumin levels (Fig. 2J) as observed in human clinical trial (21). These antifibrotic effects of linagliptin in diabetic mice are associated with a suppressed trend of TGF-b1 and DPP-4, and significant suppression of TGF-b2 protein levels in the kidney (Fig.…”
Section: Resultsmentioning
confidence: 56%
“…Urine albumin levels were elevated in STZ mice, and linagliptin treatment suppressed the trend of the urine albumin levels (Fig. 2J) as observed in human clinical trial (21). These antifibrotic effects of linagliptin in diabetic mice are associated with a suppressed trend of TGF-b1 and DPP-4, and significant suppression of TGF-b2 protein levels in the kidney (Fig.…”
Section: Resultsmentioning
confidence: 56%
“…SGLT2 inhibition has similar anti-albuminuric effects in animal models of type 2 diabetes [21], including recent evidence that empagliflozin reduced albuminuria, independent of effects on BP or hyperglycaemia, in BTBR ob/ob mouse models of type 2 diabetes [22]. Previous clinical studies in type 2 diabetes patients with and without CKD have shown that SGLT2 inhibition is associated with an acute but modest decline in eGFR within 3-6 weeks of treatment initiation, followed by a period of stable renal function for 52-104 weeks; this change is reversible after drug cessation for 2 weeks [17,23,24]. Notably, within this same treatment period, renal safety assessments of SGLT2 inhibitors have also reported a reduction in UACR or urinary albumin excretion in patients with type 2 diabetes and CKD [15,24].…”
Section: Discussionmentioning
confidence: 99%
“…Endpoints The primary assessment of this pooled analysis was defined as percentage change in geometric mean of the UACR from baseline to week 24 as described for other drug interventions targeting albuminuria [16,17]. Empagliflozin 10 and 25 mg doses were pooled to define the overall magnitude of the drug effect compared with placebo.…”
Section: Methodsmentioning
confidence: 99%
“…16 Linagliptin administered in addition to stable renin-angiotensin-aldosterone system inhibitors led to a significant reduction in albuminuria in patients with type 2 diabetes and renal dysfunction. 17 Furthermore, we have recently found that linagliptin could inhibit renal damage in streptozotocin (STZ)-induced diabetic rats (STZ rats) by suppressing the AGE-RAGE axis. 18 Since linagliptin did not improve hyperglycemia in STZ rats, our findings suggest that inhibition of DPP-4 might have glucose-lowering-independent, AGE-RAGE-axis suppressive pleiotropic actions on diabetic nephropathy.…”
mentioning
confidence: 99%
“…[15][16][17] Indeed, linagliptin, an inhibitor of DPP-4, ameliorated kidney fibrosis in type 1 diabetic mice by blocking the endothelial-tomesenchymal transition. 16 Linagliptin administered in addition to stable renin-angiotensin-aldosterone system inhibitors led to a significant reduction in albuminuria in patients with type 2 diabetes and renal dysfunction.…”
mentioning
confidence: 99%